Effects of smoking on health outcomes in bipolar disorder with a special focus on suicidal behavior. (October 2012) - Dome, Peter; Gonda, Xenia; Rihmer, Zoltan
SUMMARY  Bipolar disorder (BPD) is a common and devastating mental illness. The life expectancy for patients with BPD is significantly less than for members of the general population. The main causes for excess mortality in bipolar patients are cardiovascular disorders and, to a lesser degree, suicide. Smoking/nicotine dependence is a highly comorbid condition in patients with BPD and it has a well-known role in the etiopathogenesis of cardiovascular disorders and, according to results from the general population, is associated with elevated risk of suicidal behavior. In this literature review, the results of studies on the abovementioned associations and also the effects of comorbid smoking on clinical characteristics of BPD are summarized, with a special focus on suicidal behavior. To identify peer-reviewed research papers and reviews, databases (PubMed and Web of Science) and forward/backward citation searches were used with the following keywords: 'smoking', 'tobacco', 'nicotine', 'suicide' and 'BPD'. Only publications in English were considered.